Low-cost off-grid automatic hydroponic forage barley production system - Sanchez-Garcia, Miguel; Morsli, Hamza (International Center for Agricultural Research in the Dry Areas, 2022)
Hydroponic forage production is a viable option to provide farmers with a source of highly palatable forage at times of the year when other sources are not available. However, hydroponic forage production systems are often expensive to purchase and run and highly technologic, which makes repairing them complicated. In addition, they normally need to be connected to a source of electricity, reducing the places where they can be installed. In this report, we present a low-cost and off-the-grid solution that, coupled with elite genotypes selected for forage productivity, can produce 150-200kg of fresh barley forage every 7 days.